The animal that therefore we are conserving: conservation biology under the eyes of animality - Lamberti, Matias; di Pasquo, Federico (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Biodiversity loss has become one of the most relevant issues of our time in the context of environmental crisis. Conservation biology has established itself, since the 1980s, as the scientific field par excellence aimed at addressing this loss(1). Under the argument that their conservation results in a good chance of preserving all forms of life, animal species (particularly large mammals) have become the main focus of conservation. Now, what is the so-called animal that we are conserving? The aim of this presentation is to problematize the conception of the animal in conservation biology, and then to think about what other animalities and ways of linking ourselves are possible. To do so, we will make use of certain approaches offered by the field of critical animal studies, which questions the human/animal dichotomy that leads to an inferiorization of the animal with respect to the human(2,3,4). Thus, we will recover the hypothesis proposed by Jacques Derrida in The animal that therefore I am: generally it is possible to recognize the discourse of experts who, although they have observed and analyzed the animal, have never recognized the gaze of an other who also observes them(5). Through this anthropocentric conception of the animal that would mobilize this field of biology, a hierarchical or speciesist treatment of non-human animals is enabled in conservationist contexts. The challenge, then, will be to rethink conservation biology in order to devise non-speciesist ways of dealing with biodiversity loss